Effect of dehulling, fermentation, and roasting on the nutrient and anti-nutrient content of sorghum and pearl millet flour - Blessing Nhamoinesu Gwekwe; Prosper Chopera; Tonderayi M Matsungo; Catherine Chidewe; Stanley Mukanganyama; Elijah Nyakudya; Florence Mtambanengwe; Paul Mapfumo; Loveness K K Nyanga (International Journal on Food, Agriculture and Natural Resources, 2024)
Sorghum and pearl millet contain anti-nutritional factors such as tannins and phytic acid, which limits their use in processed food products.  Pre-treatment processes of these traditional grains such as dehulling, roasting, and fermentation, have potential to reduce the anti-nutritional factors. However, there is death in data on their efficacy.  Therefore, this study aimed to evaluate the effect of dehulling, fermenting and roasting on the proximate, micronutrient and anti-nutritional content of sorghum and pearl millet flour from Zimbabwe. The grains were roasted, dehulled, fermented, and milled into flour. Four treatments namely, (1) unprocessed sorghum (control 1), (2) processed sorghum, (3) unprocessed pearl millet (control 2) and (4) processed pearl millet were prepared. The treatment samples were evaluated for proximate and mineral content using standard methods of analysis (AOAC, 2000) and inductively coupled plasma atomic emission spectrophotometry (ICP-OES) method, respectively.  Phytates and tannins were measured using the UV Spectrophotometer method. The alkaloid content was determined gravimetrically. Data were analysed statistically using ANOVA at 95% probability. Sorghum processing i.e. dehulling, fermenting, roasting and milling significantly increased the protein content (from 15.0±0.08 to 20.0±3.98%) and ash content (from 3.6±0.05 to 4.2±0.52%) (p<0.05). No significant difference in fat content was observed between the processed and unprocessed sorghum and pearl millet (p>0.05). Similarly, the protein content of pearl millet significantly increased after processing (from 20.0 ±0.07 to 25±2.875) (p<0.05), while carbohydrate and ash content reduced significantly after processing (p<0.05). The processed pearl millet had significantly higher moisture content than the unprocessed (p<0.05). No significant difference in the calcium, iron and sodium content was recorded between the processed and unprocessed sorghum (p>0.05). The magnesium content decreased significantly after processing sorghum (p<0.05). However, potassium and zinc content increased significantly after processing (p<0.05). Processing pearl millet significantly increased in the calcium, potassium and zinc content (p<0.001). No significant difference in the iron content was observed between the two treatments (p>0.05). The magnesium and sodium content decreased significantly after processing (p<0.001). Processing pearl millet and sorghum significantly reduced the phytic acid content and tannin levels (p<0.05). The alkaloid content of the processed sorghum decreased significantly, while no significant difference in alkaloid content was recorded between processed and unprocessed pearl millet (p>0.05). Processing of sorghum and pearl millet is recommended since it improves the nutritional composition and lowers anti-nutritional factors.